Equity markets integration among us and ASEAN-5 countries - Chiu, Pik Lan (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study examines the equity market integration among United states (US) and ASEAN-5 (Malaysia, Thailand, Singapore, Indonesia and Philippines) countries. The monthly stock market closing indexes from January 2005 to December 2011 have been adopted.